The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s10853-017-1727-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of aluminum diboride products using 27Al, 11B NMR and ab initio studies

Abstract: Understanding different bonding environments in various metal borides provides insight into their structures and physical properties. Polycrystalline aluminum diboride (AlB 2 ) samples have been synthesized and compared both with a commercial sample and with the literature. One issue that arose is the relative ease with which boron-rich and aluminum deficient phases of aluminum borides can be presented in AlB 2 . Here, we report 27 Al, 11 B nuclear magnetic resonance (NMR) spectroscopy and first-principles ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In the referred spectrum, two additional peaks at 1640 and 0 ppm were assigned to elemental Al and aluminum oxide, Al 2 O 3 , respectively, impurities claimed to be inevitably present in the samples. At this point, it is important to recall that the experimental shifts of these two latter compounds have already been successfully predicted with the GIPAW method and with the same PBE PAW data sets used in this work, , which indicates a fair possibility of revisiting the peak assignments made in the literature for AlB 2 spectra, proposing that the actual experimental shift of pure AlB 2 contributes to the sharp and intense peak around 1680 ppm in the spectrum reported in ref and not to the broad peak at 880 ppm. Naturally, this also further explains the huge disagreement between the experimental 27 Al chemical shift of AlB 2 and its theoretical counterpart, as depicted in Figure .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In the referred spectrum, two additional peaks at 1640 and 0 ppm were assigned to elemental Al and aluminum oxide, Al 2 O 3 , respectively, impurities claimed to be inevitably present in the samples. At this point, it is important to recall that the experimental shifts of these two latter compounds have already been successfully predicted with the GIPAW method and with the same PBE PAW data sets used in this work, , which indicates a fair possibility of revisiting the peak assignments made in the literature for AlB 2 spectra, proposing that the actual experimental shift of pure AlB 2 contributes to the sharp and intense peak around 1680 ppm in the spectrum reported in ref and not to the broad peak at 880 ppm. Naturally, this also further explains the huge disagreement between the experimental 27 Al chemical shift of AlB 2 and its theoretical counterpart, as depicted in Figure .…”
Section: Resultssupporting
confidence: 61%
“…In a recent study, Turner et al 63 brought up challenges in synthesizing pure AlB 2 and hence in obtaining an ssNMR spectrum with the only broad peak at 880 ppm expected for this compound. In the referred spectrum, two additional peaks at 1640 and 0 ppm were assigned to elemental Al and aluminum oxide, Al 2 O 3 , respectively, impurities claimed to be inevitably present in the samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, the experimental reference does not distinguish between both 11 B species (−10.3 ppm) leaving it open whether this is caused by (solvation) effects which are not included here or from different accuracies of GIAO and GIPAW. Similarly, B (4,6,8,11) and B(9,10) in (15) are indistinguishable by experimental observation. In both cases, GIPAW predicts those accidental degeneracies more accurately than GIAO.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…In this regard, ab initio calculations of the electronic structure indicated that a deficiency of aluminum in the measured probe of AlB 2 caused a reduction of the measured 27 Al shift. 6 These are just a few of numerous examples that the literature draws a close connection between bonding situations and measurable magnetic parameters of NMR in general.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation